2022
DOI: 10.1007/s00167-022-06975-8
|View full text |Cite
|
Sign up to set email alerts
|

Patch augmentation does not provide better clinical outcomes than arthroscopic rotator cuff repair for large to massive rotator cuff tears

Abstract: Purpose Patch augmentation for large and massive rotator cuf tears (LMRCTs) has been suggested as a repair strategy that can mechanically reinforce tendons and biologically enhance healing potential. The purpose of this study was to determine whether patients who underwent patch augmentation would have lower rates of retears and superior functional outcomes. Methods Patients who underwent arthroscopic rotator cuf repair (ARCR) with patch augmentation (group A) were matched by age, sex, degree of retraction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is an important avenue to pursue. The adhesive patch also opens the door to hybrid models, where a suture could be enhanced by the addition of a patch, as studied in the treatment of massive rotator cuff tears [52]. The patch would facilitate a more even and effective distribution of stresses on the suture.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important avenue to pursue. The adhesive patch also opens the door to hybrid models, where a suture could be enhanced by the addition of a patch, as studied in the treatment of massive rotator cuff tears [52]. The patch would facilitate a more even and effective distribution of stresses on the suture.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the benefits of allograft tissue in this context are limited by variable donor quality, lack of biomimetic structures, challenges associated with arthroscopic surgical delivery, and impaired healing [8]. Moreover, the use of allograft tissue for augmentation of RCRs has not been reliably associated with significant clinical benefits compared to sutureonly repairs [9]. Recently, a reconstituted freeze-dried bovine type I atelocollagen sponge exhibited a 6-12 month in situ remodeling period to help promote RCR healing via collagen biointegration.…”
Section: Introductionmentioning
confidence: 99%
“…de Andrade et al [ 9 ] found that the range of shoulder-forward flexion tended to be lower with patch augmentation. Choi et al [ 10 ] reported that clinical outcomes and range of shoulder motion did not differ between the patch augmentation group and repair only group. However, others have reported that forward elevation was increased, suggesting that patch augmentation has not yielded promising results for shoulder range of motion [ 11 , 12 ].…”
mentioning
confidence: 99%